Improving student collaboration and critical thinking skills through ASICC model learning. Issue 1 (March 2021) - Santoso, A M; Primandiri, P R; Zubaidah, S; Amin, M
Abstract: Previous study at three leading high school in East Java have revealed that student's higher order thinking skills are good but their collaboration skills are still low. This study was aimed to reveal the effect of implementation the ASICC problem-based learning model on student's critical thinking and collaboration skills. The study included quasi-experimental research with a non-equivalent pre-post test control group design in second grade students in three leading high school in East Java. All instruments used are valid and reliable. Collaboration data that were normally and homogeneous were analyzed by t-test. The correlation between collaboration skills with critical thinking was analyzed with Pearson's correlation. This study revealed that there were significant differences in student's collaboration scores in the experimental and control classes. The ASICC class collaboration score is higher than the control class. There was a positive correlation between the ability of collaboration with critical thinking (r = 0.78). The ASICC learning model can be used as one of promising learning model to improve student collaboration skills and maintain critical thinking skills.